2012
DOI: 10.1085/jgp.201110763
|View full text |Cite
|
Sign up to set email alerts
|

Plasmin and chymotrypsin have distinct preferences for channel activating cleavage sites in the γ subunit of the human epithelial sodium channel

Abstract: Proteolytic activation of the epithelial sodium channel (ENaC) involves cleavage of its γ subunit in a critical region targeted by several proteases. Our aim was to identify cleavage sites in this region that are functionally important for activation of human ENaC by plasmin and chymotrypsin. Sequence alignment revealed a putative plasmin cleavage site in human γENaC (K189) that corresponds to a plasmin cleavage site (K194) in mouse γENaC. We mutated this site to alanine (K189A) and expressed human wild-type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 49 publications
6
77
1
Order By: Relevance
“…Importantly, we showed that plasmin concentrations in the range of those observed in urine samples of patients with CKD were sufficient to activate ENaC currents in vitro. In previously published studies, higher plasmin concentrations have been used to show its activating effect on ENaC (9,10,24,25). However, the exposure time to plasmin in those studies was relatively short (5-30 minutes), whereas in this study, plasmin at comparatively low concentrations showed a stimulating effect on ENaC after 4 hours of exposure.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Importantly, we showed that plasmin concentrations in the range of those observed in urine samples of patients with CKD were sufficient to activate ENaC currents in vitro. In previously published studies, higher plasmin concentrations have been used to show its activating effect on ENaC (9,10,24,25). However, the exposure time to plasmin in those studies was relatively short (5-30 minutes), whereas in this study, plasmin at comparatively low concentrations showed a stimulating effect on ENaC after 4 hours of exposure.…”
Section: Discussionmentioning
confidence: 70%
“…Oocytes were collected from Xenopus laevis with the approval of the animal welfare officer for the University of Erlangen-Nürnberg as described (7,9,10). Defolliculated stages 5 and 6 oocytes were injected with complementary RNA encoding human a-, b-, and g-ENaC (0.2 ng complementary RNA per subunit of ENaC).…”
Section: Two-electrode Voltage Clamp Measurements Using Human Enac-exmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, ENaC activation by plasmin has been recently demonstrated (33,34). Both uPA (abbokinase) and tPA (alteplase) are extensively used for fibrinolytic therapy for asthma, pleural effusion, and other respiratory diseases.…”
mentioning
confidence: 99%